Effects of Radiotherapy or Radical Prostatectomy on the Risk of Long-Term Heart-Specific Death in Patients With Prostate Cancer - Guo, Yadong; Dong, Xiaohui; Yang, Fuhan; Yu, Yang; Wang, Ruiliang; Kadier, Aimaitiaji; Zhang, Wentao; Mao, Shiyu; Zhang, Aihong; Yao, Xudong (Frontiers in Oncology, 2020)
Objective The prognosis of patients with prostate cancer (PCa) has improved in recent years, but treatment-related cardiotoxicity remains unclear. This study investigated the heart-specific mortality and prognostic factors of patients with PCa after radiotherapy (RT) or radical prostatectomy (RP), and compared their long-term heart-specific mortality with that of the general male population. Materials and Methods Data was taken from the Surveillance, Epidemiology, and End Result (SEER) database. Patients with PCa were included who underwent RT or RP from 2000 to 2012, and were followed through 2015. A cumulative mortality curve and competitive risk regression model were applied to assess the prognostic factors of heart-specific mortality. Standardized mortality rates (SMRs) were calculated. Results Of 389,962 men, 49.7% and 50.3% received RP and RT, respectively. The median follow-up was 8.3 years. For patients given RT, about 9 years post-diagnosis the cumulative mortality due to heart-specific disease exceeded that due to PCa. In patients who underwent RP, cumulative mortality from heart-specific disease or PCa was comparable. Relative to the general male population, overall the heart-specific mortality of patients with PCa receiving RT or RP was not higher; but in patients aged 70-to-79 years, those given RT experienced slightly higher heart-specific mortality than the age-matched general population. Conclusions Patients with PCa treated with RT or RP overall do not incur risk of heart-specific mortality higher than that of the general male population, except for patients aged 70-to-74 years receiving RT.